1999
DOI: 10.1038/sj.bjp.0702762
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for 5‐HT7 receptors mediating relaxation of human colonic circular smooth muscle

Abstract: 5-HT 4 receptors mediate relaxation of human colon circular muscle. However, after 5-HT 4 receptor blockade (SB 204070 10 nM), 5-HT still induced a relaxation (pEC 50 6.3). 5-HT 4 receptors were suciently blocked, as the curves to 5-HT obtained in the presence of 10 and 100 nM SB 204070 were indistinguishable. This 5-HT-induced relaxation was tetrodotoxin-insensitive, indicative of a smooth muscle relaxant 5-HT receptor. This, and the rank order of potency (5-CT=5-MeOT=5-HT) suggested involvement of 5-HT 1 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
65
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 10 publications
6
65
0
Order By: Relevance
“…In the gut, studies have shown that 5-HT induces muscle relaxation by affecting 5-HT 7 receptors on smooth muscle cells in addition to neuronal 5-HT 7 receptors (55)(56)(57)(58). Although the effects of selective 5-HT 7 antagonism have been studied in several animal behavioral models where it has been shown to have anxiolytic (59-61), antidepressant (62)(63)(64), and antipsychotic-like effects (65,66), to our knowledge, no current data are available on the effects of 5-HT 7 receptor antagonists in IBD.…”
Section: Cd11cmentioning
confidence: 99%
“…In the gut, studies have shown that 5-HT induces muscle relaxation by affecting 5-HT 7 receptors on smooth muscle cells in addition to neuronal 5-HT 7 receptors (55)(56)(57)(58). Although the effects of selective 5-HT 7 antagonism have been studied in several animal behavioral models where it has been shown to have anxiolytic (59-61), antidepressant (62)(63)(64), and antipsychotic-like effects (65,66), to our knowledge, no current data are available on the effects of 5-HT 7 receptor antagonists in IBD.…”
Section: Cd11cmentioning
confidence: 99%
“…This 5-HT 7 receptor population is considered to be 'atypical', because the rat jejunum is the only peripheral tissue where stimulation of 5-HT 7 receptors leads to contraction [2]. In contrast, other smooth muscle preparations, such as the guinea pig ileum [3] and human colonic circular smooth muscle [4], are relaxed. The 5-HT 7 receptor is positively coupled to adenylyl cyclase [5] and in smooth muscle the subsequent elevation of cyclic AMP is generally agreed to cause relaxation [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In the periphery, studies have mainly concentrated on vascular and alimentary tract tissues showing that relaxation of smooth muscle is mediated by the 5-HT 7 receptor. These include porcine vena cava [5] and myometrium [6], guinea-pig ileum [7] and human colonic circular smooth muscle [8]. The exception is the rat small intestine, which to our knowledge, is the only peripheral tissue where stimulation of the 5-HT 7 receptor leads to contraction [9].…”
Section: Introductionmentioning
confidence: 99%